Identification of Landslide with Resistivity Method at Candi Industrial Area, Ngaliyan, Semarang - Nuriyana Muthia Sani; Agus Setyawan; Rahmat Gernowo (Journal of Physics and Its Applications, 2021)
Landslides can be occurred in almost every natural slope or artificial slope slowly or suddenly with or without any prior signs. The main reason for slope collapse is the increase in shear stress in the landslide, the decrease in shear strength, or both. Landslide problems can result in loss of life and property, damage to the environment, infrastructure, public facilities, and disrupt livelihood generally. Landslides can be detected by exploration of the subsurface. The geoelectrical method is one of the geophysical methods to know the change of resistance of a type of rock layer below ground level. The research aims to interpret the lithology of the subsurface in the Candi Industrial Area, Ngaliyan, Semarang using Schlumberger configuration. The results of measurements are voltage and electric current to calculate the apparent resistivity value processed by IP2Win software to determine the lithology and the slip surface area. The results present that lithology in the research area consists of sand clay, clay, and sandstone. The results showed that the locations of landslide-prone areas lie at the contact between sand clay and clay with that area at a depth of between 19.95 – 31.62 m there is one difference in the resistivity value which can be assumed to be a slip surface.The result of the research can be used to make policy rules of landslide mitigation.